2019
DOI: 10.17219/acem/104617
|View full text |Cite
|
Sign up to set email alerts
|

Biological and psychological components of depression in patients receiving IFN-alpha therapy for hepatitis C

Abstract: Background. Depressive symptoms are frequent side effects of interferon α therapy (IFN-α). Both biological and psychological processes may occur concomitantly during hepatitis C treatment.Objectives. This study was carried out to determine the impact of biological (immune response) and psychological factors on formation of depressive symptoms and major depressive disorder (MDD) during hepatitis C treatment. Material and methods.A total of 99 patients receiving pegylated IFN-α and ribavirin for chronic C type h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…According to Małyszczak et al (19), it was not neuroticism score but depressive symptoms severity before treatment that was associated with the severity of depressive symptoms among HCV patients during PEG-IFN-α2a treatment. A study by Frydecka et al (20) HCV is a primarily hepatotropic positive-strand RNA virus, but there may be various extrahepatic localizations of its replication, even in peripheral blood mononuclear cells (PBMCs) (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Małyszczak et al (19), it was not neuroticism score but depressive symptoms severity before treatment that was associated with the severity of depressive symptoms among HCV patients during PEG-IFN-α2a treatment. A study by Frydecka et al (20) HCV is a primarily hepatotropic positive-strand RNA virus, but there may be various extrahepatic localizations of its replication, even in peripheral blood mononuclear cells (PBMCs) (22).…”
Section: Resultsmentioning
confidence: 99%
“…According to Małyszczak et al (19), it was not neuroticism score but depressive symptoms severity before treatment that was associated with the severity of depressive symptoms among HCV patients during PEG-IFN-α2a treatment. A study by Frydecka et al (20) revealed that baseline MADRS score and IL6 C-174G polymorphism are risk factors of MDD among patients with chronic hepatitis C treated by PEG-IFN-α2a.…”
Section: Resultsmentioning
confidence: 99%
“…One of the important factors is genetic polymorphism, which can increase individual vulnerability to depression. Some data show that it is not psychological factors but depressive vulnerability that is associated with the severity of depressive symptoms among HCV patients treated with IFN-α [ 16 ].…”
Section: Introductionmentioning
confidence: 99%